ANALISIS PENERAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PROFITABILITAS PERUSAHAAN (STUDI KASUS PADA PT SEMEN GRESIK) - Ita noviana; Ika listyawati (MAKSIMUM, 2017)
The purpose of this study was to determine the company's ability to generate profits beforedisclosing the Corporate Social Responsibility (CSR) report and after disclosing CorporateSocial Responsibility (CSR) at PT Semen Gresik. This study uses Return On Assets as ameasure of profitability ratios. The sample uses PT Semen Gresik financial statements beforeCorporate Social Responciability (CSR) in 2003-2006 and after Corporate SocialResponciability (CSR) in 2009-2012. The data collection method used in this study issecondary data, obtained from PROPER and from the company's official website. Dataanalysis method using descriptive statistical tests, Based on the results of testing descriptivestatistics there is an increase in profitability after the Corporate Social Responciability(CSR) or Sustainability report.